Effects of Growth & Learning and Internal Business Processes on Financial Performance (Survey of Regional Water Company (PDAM) in Java) - Ikram, Syafrizal; Hanim, Wasifah; Sugiartiningsih (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to find out whether growth & learning affect financial performance; does the internal business process affect financial performance? This type of research is verification and descriptive with an analysis unit of 108 Regional Water Supply Companies (PDAMs) in Java. The analysis used is multiple regression analysis. The results of the study show that growth & learning are influential, and internal business processes influence financial performance.